The effect of graphene, silica, and natural dust particles on the performances of multiple types of solar photovoltaic modules - Israa Amer Dahham; Muhammad Ammirul Atiqi Mohd Zainuri; Ali Abdulabbas Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2023)
Desertification and industrial pollution environment can significantly degrade photovoltaic cells performance. Accumulated dust on the surface of a photovoltaic module can partially hinder incident light and consequently degrade optical to electrical energy conversion. Dust properties play a major role in deteriorating solar system performance. Thus, this paper presents extensive investigations on the UV- absorbance, light transmittance and reflectance through an accumulated dust layer. Dust characterization; focusing on its spectral and crystallographic properties of three types of dust (Graphene, Silica, and natural), was carried out to evaluate the degradation rate of the output power for three types of solar PV modules (monocrystalline, polycrystalline, and thin-film). Spectrophotometric analysis was conducted to determine UV light absorbance and light transmittance through the three types of dust. X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) tests were conducted to evaluate the effect of dust crystallinity on light reflectance. A lab-scale setup was used to examine the performances of the three solar PV modules under clean and polluted conditions. Results indicated that Graphene dust exhibits severe UV light absorbance, and its crystalline form increases light reflectance from the surfaces of the modules. However, Silica and natural dust showed a little UV absorbance. Among the three types of the solar PV modules, thin-film panel showed the highest degradation under polluted conditions as compared to the other modules. Therefore, thin film solar module is not recommended for areas with high density of dust.